Geology and geochemistry of topsoil in Ngalang, Gunungkidul Regency, Yogyakarta, Indonesia - Sharifah Nurin Wahida Syed Sabri Al Qabbani (2020)
Geographically Ngalang was located in coordinate S 7°52'07.3", S 7°52'48.25 in longitude and E 110° 34' 33.50" , E 110° 35' 15.0" in latitude. Ngalang area located Gunungkidul Regency comprise of varies unique geomorphology and geological value in its area. A geological map with larger scale; 1:25 000 had been produced through geological mapping activities process. The drainage pattern of Ngalang was decorated with dendritic and rectangular drainage pattern that fits into flat landscape and escarpment valley of its area. Lithologies of Ngalang area were grouped into four formations with different unique identities such as Bouma sequence and trace fossil (bioturbation). Four formation of this area made up of Semilir formation with of tuffaceous unit, overlies by volcanic lava and breccia unit of Nglanggeran formation, comformably overlies by intercalation of Sambipitu formation sandstone and clay unit and also carbonate sandstone with limestone characteristics in Oyo formation. Besides, interfingering area of Sambipitu and Nglanggeran was identified by conducted geological and grid mapping activities. Then, grid soil map was produced and sampling location was chosen. Topsoil in selected location was collected for geochemical analysis of topsoil and analysed by using X-Ray Fluorescence. The major element detected in the topsoil samples of the contact area was Si, Al, Fe, Ti, Mg, Ca, Mn, K, Na and P.